Establishment of Cutoff Values for Newborn Screening of Six Lysosomal Storage Disorders by Tandem Mass Spectrometry - Li, Ruotong; Tian, Liping; Gao, Qing; Guo, Yuanfang; Li, Gaijie; Li, Yulin; Sun, Meng; Yan, Yan; Li, Qing; Nie, Wenying; Zou, Hui (Frontiers in Pediatrics, 2022)
Objective Lysosomal storage disorders (LSDs) are becoming increasingly important in newborn screening, and tandem mass spectrometry (MS/MS) is widely used in newborn screening for LSDs through measurement of enzymatic activities in dried blood spots (DBSs). Overall, the determination of the cutoff value is important in such screening, and different laboratories have different methods of determining this value; most do not use a fixed cutoff value but rather calculate the corresponding batch cutoff value based on each batch of experimental data. In this study, we used MS/MS to screen for LSDs and sought to find an appropriate method to establish the cutoff value for LSD screening. Methods A total of 38,945 samples from newborn blood tablets collected from various maternity hospitals in six cities in Shandong province, including Jinan, Dezhou, Heze, Linyi, Weifang, and Zibo, were tested using a Waters Xevo TQD tandem mass spectrometer; the experimental data were analyzed with MassLynx V4.1. The laboratory used 30% of the median GLA enzyme activity and 20% of the median ABG, ASM, GALC, IDUA, and GAA enzyme activities in every test as the cutoff values for that batch of experiments. Results There were 254 suspicious positives in the initial screening test, including one case of Gaucher disease, one of Niemann-Pick disease, 47 of Krabbe disease, four of MPS-I, 21 of Fabry disease, and 180 of Pompe disease. After genetic screening, 11 children were diagnosed, including three with Pompe disease, three with Fabry disease, and five with Krabbe disease. In addition, the enzyme activity cutoff value of this experiment showed seasonal variation, which was initially believed to be related to the ambient temperature, such as the effect of ambient temperature on the human body or the temperature when the blood tablets dried naturally. Conclusion Overall, MS/MS can be used in LSD screening, and using different cutoff values in each batch of experiments is feasible. The ambient temperature might be a reason why the enzyme activity cutoff value has seasonal variation. More samples are needed to develop a method of determining cutoff values in laboratories.